Association of Maternal Prepregnancy Body Mass Index With Placental Histopathological Characteristics in Uncomplicated Term Pregnancies. (January 2019) - Brouwers, Laura; Franx, Arie; Vogelvang, Tatjana E; Houben, Michiel L; van Rijn, Bas B; Nikkels, Peter GJ
Introduction: Prepregnancy obesity is a growing global health problem and has several risks for mother and child. The aim of this study was to systematically examine the effect of increased maternal body mass index (BMI) on placental pathology in otherwise uneventful term pregnancies. Methods: In this analysis, we studied data of the Netherlands Amniotic Fluid study, a prospective study of women delivering in Utrecht, the Netherlands, between 2006 and 2007. We included women with uncomplicated pregnancies, vaginal delivery, and data on prepregnancy weight and height (n = 382). Placental histopathology was compared between women of normal BMI (≤24.9 kg/m 2 ), overweight (25–29.9 kg/m 2 ), and obese (≥30 kg/m 2 ). Results: Increasing prepregnancy BMI was associated with heavier placentas and higher mean infant's birth weight. In addition, obesity was positively associated with high-grade chronic villitis (odds ratio [OR]: 18.1, 95% confidence interval [CI]: 1.6–205.2), accelerated villous maturation (OR: 1.1, 95% CI: 1.0–1.2), and lower incidence of placental weight below the 10th percentile for gestational age (OR: 0.5, 95% CI: 0.3–1.0). There was a substantial effect of parity on maternal, placental, and neonatal weights. Conclusions: Even in uncomplicated pregnancies, maternal obesity is associated with characteristic changes in placental pathology. Further research is needed to evaluate these changes in view of later-life health of infants born to obese mothers.